(untitled) (Research, Society and Development, 2023)
The present study sought to test the association nutritional status and eating attitudes of bariatric patients in the context of the Covid-19 pandemic in Brazil. This is a cross-sectional, descriptive, analytical, online study, with 412 individuals, distributed in 21 Brazilian states, the study was carried out after approval by the Ethics Committee and contemplates female or male individuals, aged 18 years or over, who underwent bariatric surgery, and who accepted the research terms. Descriptive statistics (mean, standard deviation and frequency) were used. Pearson’s chi-square test was applied to test the association between categorical variables, with analysis of adjusted residuals to identify which categories were associated. For all analyses, the statistical significance level of p<0.05 was considered. Socio-demographic data were used: gender, education, family income, housing, surgery time, sports technique, BMI and EAT-26 sports. The results showed individuals with greater participation in the female public, with high school education and income from one to three minimum exams, such factors were associated with the development of eating attitudes, gastric bypass and individuals attended between three and six months after the procedure and the pre-surgical EAT-26 total score of value 0.47 stratified positive for TA. In this sense, continuous multidisciplinary and nutritional monitoring is essential to ensure the success of the bariatric procedure.